Exploration of the potential mechanism of Baicalin for hepatic fibrosis based on network pharmacology, gut microbiota, and experimental validation - Liu, Sujie; Chen, Pingping; Mohammed, Shadi A. D.; Li, Zihui; Jiang, Xin; Wu, Juan; Liu, Shumin (Frontiers in Microbiology, 2023)
Baicalin (BA) is among the most effective and abundant flavonoids extracted from Scutellaria baicalensis that may be utilized to treat diseases associated with hepatic fibrosis (HF). Through network pharmacology, gut microbiota, and experimental validation, this research intends to elucidate the multi-target mechanism of BA on HF. BA targets were screened using databases and literature. As a result, In the anti-HF mechanism, the BA and 191 HF-associated targets interact, with 9 specific targets indicating that the BA's anti-HF mechanism is closely linked to gut microbiota.. Consequently, rat intestinal content samples were obtained and examined using 16S rRNA sequencing. In the BA-treated group, the gut microbiota was positively regulated at the phylum,and genus levels, with Lactobacillus performing significantly. The study concluded that BA has a multi-targeted anti-HF effect and has changed the gut microbial ecosystem.